Development of a high‐sensitivity ELISA detecting IgG, IgA and IgM antibodies to the SARS‐CoV‐2 spike glycoprotein in serum and saliva. Issue 1 (24th May 2021) - Faustini, Sian E.; Jossi, Sian E.; Perez‐Toledo, Marisol; Shields, Adrian M.; Allen, Joel D.; Watanabe, Yasunori; Newby, Maddy L.; Cook, Alex; Willcox, Carrie R.; Salim, Mahboob; Goodall, Margaret; Heaney, Jennifer L.; et al.
Abstract: Detecting antibody responses during and after SARS‐CoV‐2 infection is essential in determining the seroepidemiology of the virus and the potential role of antibody in disease. Scalable, sensitive and specific serological assays are essential to this process. The detection of antibody in hospitalized patients with severe disease has proven relatively straightforward; detecting responses in subjects with mild disease and asymptomatic infections has proven less reliable. We hypothesized that the suboptimal sensitivity of antibody assays and the compartmentalization of the antibody response may contribute to this effect. We systematically developed an ELISA, optimizing different antigens and amplification steps, in serum and saliva from non‐hospitalized SARS‐CoV‐2‐infected subjects. Using trimeric spike glycoprotein, rather than nucleocapsid, enabled detection of responses in individuals with low antibody responses. IgG1 and IgG3 predominate to both antigens, but more anti‐spike IgG1 than IgG3 was detectable. All antigens were effective for detecting responses in hospitalized patients. Anti‐spike IgG, IgA and IgM antibody responses were readily detectable in saliva from a minority of RT‐PCR confirmed, non‐hospitalized symptomatic individuals, and these were mostly subjects who had the highest levels of anti‐spike serum antibodies. Therefore, detecting antibody responses in both saliva and serum can contribute to determining virus exposure and understanding immune responses after SARS‐CoV‐2 infection. Abstract : This manuscript describes the development of a highly sensitive ELISA, optimizing different antigens and amplification steps, in serum and saliva from non‐hospitalized SARS‐CoV‐2‐infected subjects. Using a trimeric spike glycoprotein, rather than nucleocapsid, enabled detection of responses in individuals with mild‐to‐moderate infection. The detection of antibodies in both serum and saliva can contribute to determining virus exposure and understanding immune responses to SARS‐CoV‐2.